Advanced Electrochemical Scaffolds for Multiplexed Biosensing of Cancer Reporters in Complex Clinical Samples. (2017) - Torrente-Rodríguez, Rebeca M.; Campuzano, Susana; Montiel, Víctor Ruiz-Valdepeñas; Eletxigerra, Unai; Martinez-Perdiguero, Josu; Merino, Santos; Barderas, Rodrigo; Villalonga, Reynaldo; Pingarrón, José M.
Abstract: Early and reliable diagnostic of cancer is mandatory to increase patient survival, thus requiring efficient and reliable analytical methods for such a purpose. Within this context, different strategies implying the development of electrochemical biosensors for the sensitive, selective and rapid multiplexed biosensing of genetic or protein cancer-related biomarkers are addressed in this presentation. In particular, novel sensing platforms have been developed for the determination of miRs, interleukin (IL)-8 mRNA, IL-8 protein, and cancer specific receptors. The developed methodologies allow for the determination of the target analytes at clinically relevant levels in complex samples: cancer cells, human tissues cell lysates, serum and raw saliva and can be easily extended to the determination of other relevant biomarkers.